2014
DOI: 10.1016/j.kjms.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous paracetamol for the prevention of rocuronium injection pain

Abstract: Rocuronium is a nondepolarizing neuromuscular blocking agent used in anesthesia induction and is associated with considerable discomfort and burning pain during injection, which is reported to occur in 50-80% of patients. This study was carried out to investigate the effectiveness of intravenous paracetamol pretreatment compared with lidocaine and normal saline to prevent rocuronium injection pain. The study included 150 ASA I-II patients undergoing elective orthopedic, gastrointestinal, and gynecological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 29 publications
2
24
0
2
Order By: Relevance
“…Parasetamolün periferik analjezik etkisinin propofol ve roküron-yum enjeksiyon ağrısını önlemedeki etkisini araştıran ça-lışmalar vardır (12,15 Roküronyum enjeksiyon ağrısını önlemede, fentanil, remifentanil gibi opioidler, ketamin, lidokain gibi ajanlar kullanılmıştır. Remifentanilin roküronyum enjeksiyon ağrısına etkisi ile ilgili araştırma sonuçları çelişkilidir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Parasetamolün periferik analjezik etkisinin propofol ve roküron-yum enjeksiyon ağrısını önlemedeki etkisini araştıran ça-lışmalar vardır (12,15 Roküronyum enjeksiyon ağrısını önlemede, fentanil, remifentanil gibi opioidler, ketamin, lidokain gibi ajanlar kullanılmıştır. Remifentanilin roküronyum enjeksiyon ağrısına etkisi ile ilgili araştırma sonuçları çelişkilidir.…”
Section: Discussionunclassified
“…Tüm incelemelerde p<0,05 istatistiksel olarak anlamlı kabul edildi. Yeterli hasta sayısını saptamak için daha önce yapılan ve lidokain ile enjeksiyon ağrısı olmama oranı %48, paracetamol kullanıldığında ise %22,5 bulunan bir çalışma referans alındı (15). Çalışmamızda lidokain ve parasetamol grupları arasındaki ağrı olmama oranları arasında %25,5 fark, tip I hata 0,05 ve %80 güç ile saptanabilmesi için gereken örnek-lem büyüklüğü her grup için minimum 43 hasta olarak hesaplandı.…”
Section: İstatistiksel Analizunclassified
“…We initially identified 84 records according to the retrieval strategy aforementioned, and 9 [10][11][12][13][14][15][16][17][18] of them involving 819 patients were included eventually according to the inclusion and exclusion criteria ( Fig. 1 PRISMA diagram showing article selection for this review).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Many clinical studies have tried to reduce the withdrawal response by various pharmacological interventions [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested that non-opioid analgesics such as tramadol and paracetamol also effectively reduced rocuronium-induced withdrawal response, even though their effects were less than that of lidocaine [4,6]. In addition, serotonin receptor antagonists such as ondansetron and palonosetron were also effective in the prevention of rocuronium-induced withdrawal response, although there is some controversy regarding the effectiveness of serotonin receptor antagonists compared to that of lidocaine [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%